2008
DOI: 10.1002/ijc.23754
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antioxidant supplementation on chemotherapeutic toxicity: A systematic review of the evidence from randomized controlled trials

Abstract: Much debate has focused on whether antioxidants interfere with the efficacy of cancer chemotherapy. The objective of this study is to systematically review the randomized, controlled clinical trial evidence evaluating the effects of concurrent use of antioxidants with chemotherapy on toxic side effects. We performed a search of literature from 1966‐October 2007 using MEDLINE, Cochrane, CinAhl, AMED, AltHealthWatch and EMBASE databases. Randomized, controlled clinical trials reporting antioxidant‐based mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(164 citation statements)
references
References 54 publications
3
154
0
7
Order By: Relevance
“…The chronic poisoning symptoms include: feeling of chronic fatigue, irritability, double vision, nystagmus, sleep disturbances, cracking and bleeding lips and gums, shedding of hair, rashes and ulceration of the skin, muscular coordination disturbances, renal dysfunction (haematuria), and even oedema of the optic disc and other symptoms that could suggest a brain tumor. Hypervitaminosis A can also lead to auditory sensations which are not caused by any sound stimulus (parestesia) [22,23,28,29]. The excessive intake of vitamin A affects harmfully the haematopoietic system, leading to aplastic anemia.…”
Section: Biomedical Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic poisoning symptoms include: feeling of chronic fatigue, irritability, double vision, nystagmus, sleep disturbances, cracking and bleeding lips and gums, shedding of hair, rashes and ulceration of the skin, muscular coordination disturbances, renal dysfunction (haematuria), and even oedema of the optic disc and other symptoms that could suggest a brain tumor. Hypervitaminosis A can also lead to auditory sensations which are not caused by any sound stimulus (parestesia) [22,23,28,29]. The excessive intake of vitamin A affects harmfully the haematopoietic system, leading to aplastic anemia.…”
Section: Biomedical Actionmentioning
confidence: 99%
“…Toxic effects appear when the ability of plasma RBP (retinol binding proteinthe carrier for vitamin A in blood) to bind retinol and to conjugate its excess with glucuronate is exceeded, which leads to harmful exposure of the cells to free vitamin A [14,22,23]. Patients with hepatic and renal diseases and children are especially susceptible to the adverse effects of this vitamin.…”
Section: Potential Riskmentioning
confidence: 99%
“…Many studies, though, have demonstrated that oxidative stress is responsiple for chemotherapeutic druginduced liver toxicology [11] . In mitigation of chemotherapy side effects, some antioxidant drugs or agents with anticancer effects have been determined helpful depending on the reducing effect on oxidative stress [12] . Many studies have shown that beta-1,3-D-glucan, an antioxidant and anti-cancer agent, has protective antioxidant activity against chemotherapy-induced liver toxicity [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Against this background it is evident that a supportive nutrition therapy should be an integral part of cancer care (44)(45)(46). In addition to a sufficient supply of energy substrates, vitamins and minerals as well as long-chain ˆ-3 fatty acids are becoming more and more interesting (31, [47][48][49][50][51][52][53][54][55][56], although the therapeutic benefit of such supplements is the subject of a controversial discussion, especially in respect ONCOLOGY REPORTS 24: 815-828, 2010 of supplements with high concentrations of antioxidants like the vitamins C and E and the trace element selenium (57)(58)(59)(60)(61)(62)(63)(64)(65)(66).…”
Section: Introductionmentioning
confidence: 99%